Mechanism of the process of photochemical metallization of dielectric surfaces - Abdurazova, P.A.; Koshkarbayeva, Sh.T.; Satayev, M.S.; Dzhakipbekova, N.O.; Raiymbekov, Ye.B. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The possibility of applying copper-containing films on the surfaces of various samples was investigated in the paper. Flat and smooth copper plates and fabric were used for the study. The sample of dielectric material was immersed in the solution, then they were dried in the sun, and work was done on the deposition of copper on the surface of the sample. The study of the rate of photochemical reduction of copper showed that the process consisted of two stages. In the first 30 minutes of the first stage, by increasing the concentration of Halogens during drying of the coating, a semiconductor layer is formed, and in the second — the direct photochemical reduction of copper, which takes about 30 minutes, but then gradually slows down. At the second stage, the rate of the photochemical reaction is equal to the rate of chemical or galvanic metallization. As a result of the photochemical reaction, when drying the sorption layer under the influence of sunlight, copper semiconductors are formed, which shape metallic coatings on the surface. This, in turn, can be used to make thinner films.
Диэлектрлік беттерді фотохимиялық металдау процесінің механизмі
Механизм процесса фотохимической металлизации диэлектрических поверхностей
Keywords: mechanism; photochemistry; metallization; dielectric surface; copper; reaction; coating; films